Suitable fertilization can improve maize growth and nutrient utilization in ridge-furrow rainfall harvesting cropland in semiarid area - Wang, Jiayi; Liu, Gaoxiang; Cui, Nan; Liu, Enke; Zhang, Yan; Liu, Donghua; Ren, Xiaolong; Jia, Zhikuan; Zhang, Peng (Frontiers in Plant Science, 2023)
The ridge-furrow rainfall harvesting system (RFRH) improved the water shortages, and reasonable fertilization can promote nutrient uptake and utilization of crops, leading to better yield in semi-arid regions. This holds significant practical significance for improving fertilization strategies and reducing the application of chemical fertilizers in semi-arid areas. This field study was conducted to investigate the effects of different fertilization rates on maize growth, fertilizer use efficiency, and grain yield under the ridge-furrow rainfall harvesting system during 2013-2016 in semiarid region of China. Therefore, a four-year localization field experiment was conducted with four fertilizer treatments: RN (N 0 kg hm-2, P2O5 0 kg hm-2), RL (N 150 kg hm-2, P2O5 75 kg hm-2), RM (N 300 kg hm-2, P2O5 150 kg hm-2), and RH (N 450 kg hm-2, P2O5 225 kg hm-2). The results showed that the total dry matter accumulation of maize increased with the fertilizer application rate. The nitrogen accumulation was highest under the RM treatment after harvest, average increase by 1.41% and 22.02% (P<0.05) compared to the RH and RL, respectively, whereas the phosphorus accumulation was increased with the fertilizer application rate. The nitrogen and phosphorus use efficiency both decreased gradually with the fertilization rate increased, where the maximum efficiency was observed under the RL. With the increase of fertilizer application rate, the maize grain yield initially increased and then decreased. Under linear fitting, the grain yield, biomass yield, hundred-kernel weight, and ear-grain number all showed a parabolic trend with the increase of fertilization rate. Based on comprehensive consideration, the recommended moderate fertilization rate (N 300 kg hm-2, P2O5 150 kg hm-2) is suitable for the ridge furrow rainfall harvesting system in semiarid region, and the fertilization rate can be appropriately reduced according to the rainfall.